Air Force combat controllers what it takes to join the elite - Stilwell, Alexander (New York Cavendish Square, 2015)
Presents the requirements, skills and equipment of the U.S. Air Forces special land force, the Combat Controllers.
Selection and training -- History -- What it takes -- Special tactics squadrons -- Combat control selection course -- Combat control operator course -- Special tactics advanced skills I -- Special tactics advanced skills II -- Special skills -- Specialist parachuting -- Combat diving -- Submarine operations -- Scout swimming -- Survival skills (SERE) -- Mountain operations -- Navigation and communications -- Setting up assault zones -- Special equipment -- Aircraft -- Wheeled vehicles -- Rifles and handguns -- In action -- Fighting the Taliban -- Operations in Iraq -- Glossary.
Includes bibliographical references (page 47) and index.
12 - 17 years
104786
Keywords: United States. -- Air Force -- Commando troops; United States. -- Air Force; Close air support -- Study and teaching; Special forces (Military science) -- United States; Armed Forces -- Commando troops; Close air support -- Study and teaching; Special forces (Military science)